2002
DOI: 10.1021/la010657d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of X-ray Irradiation on the Chemical and Physical Properties of a Semifluorinated Self-Assembled Monolayer

Abstract: The effect of X-ray irradiation on the chemical and physical properties of a semifluorinated self-assembled monolayer (CF-SAM) derived from 1H,1H,2H,2H-perfluorodecanethiol (CF3(CF2)7(CH2)2SH) adsorbed on gold and copper substrates was studied using X-ray photoelectron spectroscopy. During the initial period of irradiation, the effects of electron-stimulated C-F, C-C, and S-X (X ) Au, Cu) bond breaking are responsible for changes in the chemical composition of the CF-SAM. Furthermore, the evolution of the C(1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 39 publications
(102 reference statements)
5
51
0
Order By: Relevance
“…A small CF peak is also observed, whose presence is attributed to the effects of low-energy electrons generated by X-ray irradiation during the XPS scan. 12,13 This assertion is supported by the effect that prolonged X-ray irradiation was observed to have on the C(1s) region of the PFOTS monolayer (see Figure 1). …”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…A small CF peak is also observed, whose presence is attributed to the effects of low-energy electrons generated by X-ray irradiation during the XPS scan. 12,13 This assertion is supported by the effect that prolonged X-ray irradiation was observed to have on the C(1s) region of the PFOTS monolayer (see Figure 1). …”
Section: Resultsmentioning
confidence: 73%
“…The changes in both the C(1s) spectral envelope and integrated C(1s) area as a function of increasing X-ray irradiation time are analogous to the previously observed effects of X-ray and electron beam modifications of semifluorinated SAMs on metal substrates. 12,13,35 Thus, for comparatively short irradiation times (<60 min), a rapid decrease is observed in the C(1s) and F(1s) XPS areas (carbon data shown in Figure 5, fluorine data not shown). These chemical changes are consistent with the ejection of CF x and F -species due to electronstimulated C-C, C-F, and C-H bond cleavage processes within the PFOTS monolayer ( Figure 8).…”
Section: Discussionmentioning
confidence: 97%
“…This is especially the case for the high temperature measurements, which take place after a large cumulative dose, and for the fluorocarbon samples, which are known to be susceptible to X-ray induced desorption/ decomposition [33,34]. C-F bond cleavage results from secondary electrons, and this could in part be responsible for a fraction of the decreasing F signal.…”
Section: Resultsmentioning
confidence: 99%
“…15 The S(2p) region consists of a single doublet at 162.8 eV associated with the 2p 3/2 and 2p 1/2 transitions of native thiolate species bound to the underlying Au substrate. 9,15,25 The Au(4f) region is composed of two peaks at 84 eV and 87.6 eV due to the 4f 7/2 and 4f 5/2 transitions of metallic Au.…”
Section: Methodsmentioning
confidence: 99%
“…Such an analysis reveals that the effective diffusion length (or penetration depth) of atomic O within the hydrocarbon film is ≈5.5 Å. Furthermore, the fact that Au 2 O 3 and RSO 3 species are not observed until after prolonged O/O 2 exposure indicates that although X-ray irradiation of SAMs induces carbon, sulfur, and hydrogen desorption 25,26 the X-ray-modified C 16 -SAM forms a 3-dimensionally dense overlayer, preventing O-atom penetration to the film/vacuum interface (Scheme 1). These results are consistent with those of George et al 9 who found that carbon oxidation and C-C bond cleavage occur prior to oxidation at the film/substrate interface.…”
Section: Scheme 1: Schematic Of the Interaction Of O/o 2 With A C 16 mentioning
confidence: 99%